The effects on local livelihoods of a Wetland development scheme in a Zimbabwean village : an ethnographic study - Mangoma, Jaqualine Farai (Social Anthropology, 2015)
This study explores the effect on local livelihoods of the New Gato Wetland Development Project (NGWP) in a rural village in Zimbabwe, in light of a post development critique which has labelled most development as a failure.